2019
DOI: 10.19128/turje.435345
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mathematics achievement: The role of perceived feedback, teacher support and self-beliefs

Abstract: In this study, the mediating roles of perceived teacher support and students' mathematics self-beliefs on the feedback process were investigated in The Programme for International Student Assessment (PISA) context in Turkey. PISA 2012 mathematics scores and questionnaire responses of 4848 15-year-old students were analyzed. Results indicated that perceived feedback was positively related to math selfconcept and negatively related to math anxiety. The investigated indirect effects were partly confirmed: perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Students who felt supported by their teachers showed higher performance in reading literacy. Several studies also reported that teachers' support was associated with students' higher academic performance (Ma et al, 2021;Ricard & Pelletier, 2016;Yıldırım, 2012;Yıldırım & Yıldırım, 2019). Adaptation of instruction showed a significant relationship with reading l iteracy.…”
Section: Discussionmentioning
confidence: 94%
“…Students who felt supported by their teachers showed higher performance in reading literacy. Several studies also reported that teachers' support was associated with students' higher academic performance (Ma et al, 2021;Ricard & Pelletier, 2016;Yıldırım, 2012;Yıldırım & Yıldırım, 2019). Adaptation of instruction showed a significant relationship with reading l iteracy.…”
Section: Discussionmentioning
confidence: 94%
“…It is possible to come across studies in which the concept of competency is used in different meanings. For example, while Adıgüzel (2017) and S. Yıldırım and Yıldırım (2019) use "competency" as "proficiency", Özkal (2018) uses it accurately as "competency." Based on this, in this study which aims to reach a conceptual consensus, the agreed definition of "competence" is the definition provided in the TQF (MYK 2015, 19).…”
Section: Discussionmentioning
confidence: 99%
“…Teacher support is positively associated with student motivation (Ryan & Patrick, 2001) and engagement (Skinner, Furrer, Marchan, & Kindermann, 2008;Strati, Schmidt, & Maier, 2017). Teacher support indirectly affects students' mathematics achievement (Yıldırım, 2012;Yıldırım & Yıldırım, 2019;Yu & Singh, 2018) and their interest in mathematics lessons (Yu & Singh, 2018) through students ' math self-efficacy. Teacher support can be seen as an important factor in removing barriers to effective teaching, as it is negatively associated with school problems, inattention, and hyperactivity disorders (Tennant et al, 2014) and has a positive effect on peer conflict resolution (Wang et al, 2014).…”
Section: Teacher Supportmentioning
confidence: 99%